Upaya Mengembangkan Kader Dan Mengoptimalkan Penurunan Tingkat Hipertensi Pada Masyarakat - Estrin Handayani; Muhammad Abdul Aziz; Putri Ardianti; Audyna Navisa Larasati; Fina Amalia; Muhammad Yusuf Safri Mabruri (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
the average prevalence of hypertension in indonesia is 31.7%; by 2025, the proportion of hypertensive patients is projected to increase to 24% in developed countries and 80% in developing countries. prevention and monitoring of hypertension can be done through community health centers or the posyandu program. participants providing community service are characterized by staff who supervise people with hypertension, the most common disease. this service is carried out through active lectures and discussions with participants. the activities show that cadres already know about hypertension and know how to prevent complications and how cadres regularly measure blood pressure independently. therefore, there is a need for creative health promotion initiatives and targeting the right people/groups so that better changes can be made in the future.keywords: blood pressure; cadre; hypertension; skills; knowledge.